Assessment of “Proning” Nursing Intervention to Increase ROX Index in COVID-19 Patients: A Literature Review - Martono, Martono; Khadijah, Siti; Fernanda, Pradita Ayu (Poltekkes Kemenkes Surakarta, 2025)
Background: COVID-19 has become a global crisis that has created public health problems. The impact of COVID-19 infection primarily affects the respiratory tract. The most prominent impairments in COVID-19 infection include difficulty breathing and decreased blood oxygen saturation. This review aims to identify available literature related to the effects of proning techniques on improving respiratory rate and oxygenation (ROX) indices, namely SPO2 and PaO2/FiO2 fractions, in patients with acute respiratory distress syndrome (ARDS) due to COVID-19. Methods: A literature review design was employed. An online search strategy was conducted using major electronic databases, including Scopus, PubMed, Science Direct, ProQuest, and Google Scholar. This review design used the Preferred Reporting Items for Systemic Review and Meta-Analysis (PRISMA) Guidelines. The literature sources reviewed ranged from 2020 to 2025. Ten articles met the criteria and were reviewed. Results: A total of 387 articles met the screening criteria: 159 articles were identified after screening for duplication, 25 articles met the criteria for full-text review and eligibility, and 15 articles were excluded due to study design and irrelevant results. Ten articles met the criteria and were reviewed. Conclusion: Proning is the use of a prone position that can improve the body's oxygenation adequacy index, both ROX with the SpO₂ indicator and the PaO₂/FiO₂ ratio, and these findings highlight the health practice that healthcare professionals play a key role in assessing oxygenation status, safely applying prone positioning, and closely monitoring patient responses to optimize respiratory outcomes.